Impact of Age on Outcomes in Hospitalized Patients with Hereditary Hemorrhagic Telangiectasia - Vivek N. Iyer; Waleed Brinjikji; Dinesh Apala; Bibek S. Pannu; Aditya Kotecha; Michael D. Leise; Patrick S. Kamath; Sanjay Misra; Giuseppe Lanzino; Michael J. Krowka; Christopher P. Wood; Karen L. Swanson (Advances in Hematology)
Background. There is little published literature regarding the impact of age on outcomes amongst hospitalized HHT (hereditary hemorrhagic telangiectasia) patients. Methods. The Nationwide Inpatient Sample (NIS) was used to obtain data on all hospital discharges occurring in HHT patients from 2000 to 2012. The association between admission age and HHT-related complications and outcomes were studied. Results. 10293 hospitalizations in HHT patients from 2000 to 2012 were included. Patients > 50 accounted for 77% of all admissions with 30% of admissions occurring in the 51–65 age group. Bleeding related complications were the most frequent (62.7%, n=6455 hospitalizations), followed by cardiovascular (41%, n=4216), neurological (12.4%, n=1276), and hepatobiliary (6.4%, n=660) complications. Patients older than 50 accounted for 83% of bleeding events, 90% of cardiovascular events, 58% of neurologic events, and 81% of hepatobiliary events. The vast majority (83%) of medical and surgical procedures were performed in those older than 50 years of age. Older patients also experienced higher rates of death. Conclusion. Aging has significant adverse impacts on rates of hospitalization, complications, and outcomes amongst HHT patients in the United States. Except for neurologic complications, the vast majority of this disease burden is borne by patients older than 50 years.